Second-order problem solving: Nurses' perspectives on learning from near misses - Yi Yang; Huaping Liu; Gwen D. Sherwood (Elsevier, 2021)
Objectives: Near misses happen more frequently than actual errors, and highlight system vulnerabilities without causing any harm, thus provide a safe space for organizational learning. Second-order problem solving behavior offers a new perspective to better understand how nurses promote learning from near misses to improve organizational outcomes. This study aimed to explore frontline nurses' perspectives on using second-order problem solving behavior in learning from near misses to improve patient safety. Methods: A qualitative exploratory study design was employed. This study was conducted in three tertiary hospitals in east China from June to November 2015. Purposive sampling was used to recruit 19 frontline nurses. Semi-structured interviews and a qualitative directed content analysis was undertaken using Crossan's 4I Framework of Organizational Learning as a coding framework. Results: Second-order problem solving behavior, based on the 4I Framework of Organizational Learning, was referred to as being a leader in exposing near misses, pushing forward the cause analysis within limited capacity, balancing the active and passive role during improvement project, and promoting the continuous improvement with passion while feeling low-powered. Conclusions: 4I Framework of Organizational Learning can be an underlying guide to enrich frontline nurses' role in promoting organizations to learn from near misses. In this study, nurses displayed their pivotal role in organizational learning from near misses by using second-order problem solving. However, additional knowledge, skills, and support are needed to maximize the application of second-order problem solving behavior when near misses are recognized.